THU0604 Disease Activity and Biologic Use in Patients with Rheumatoid Arthritis and Psoriatic Arthritis in The Past 10 Years: Results from The Corrona Registry. (15th July 2016) - Kavanaugh, A.; Griffith, J.; Karki, C.; Etzel, C.J.; Kremer, J.M.; Greenberg, J.D.; Ganguli, A.
Abstract : Background: While some treatment options for psoriatic arthritis (PsA) are similar to those initially developed for rheumatoid arthritis (RA), their introduction to the clinic has generally increased in the recent years. Also, there has been a perception among some that RA is perhaps associated with greater disease burden compared to PsA. Objectives: The objective of this study was to determine and compare the disease activity related to peripheral arthritis and biologic use in patients with RA and PsA over the past 10 years in Corrona registry. Methods: All patients between 01/2002 – 03/2013 were included and patients were grouped in 2 year intervals 2002–2003, 2004–2005, 2006–2007, 2008–2009, 2010–2011, 2012–2013. Within each time period, standardized differences were used to identify patient characteristics that were different between PsA and RA patients. Logistic regression models evaluated the likelihood of being in moderate/high clinical disease activity index (CDAI) and use of biologics in PsA patients compared to patients with RA, adjusting for covariates within each time period. Random effects logistic regression models were also considered to account for site random effects. Results: A total of 20982 and 2552 RA and PsA patients respectively were studied over the six time intervals. The mean age was 59 yrs and 53 yrs for RA and PsA patients respectively. Mean CDAI and percentage of patients in moderate/severe disease activity were significantly higher in RA and PsA over the years; disease activity generally decreased over time for both (Figure ). History of biologic use was similar between the two groups in 2002–03 (44% in RA vs 42.5% in PsA), however there was an upward trend in biologic use in both groups with higher use among PsA patients over the past years (figure ). Similarly current biologic use also increased from 36.3% vs 36.1% in RA vs PsA in 2002–03 to 52.1% vs 62% in 2012–2013 respectively. Adjusted models showed that PsA patients were significantly less likely to be in moderate/severe disease activity defined by CDAI (OR (95% CI): 0.79 (0.72, 0.88)) over the past years and more likely to be on a biologic compared to RA patients in 2012–13 (Odds ratio (95% CI): 1.37 (1.25, 1.49)). Conclusions: Although disease activity has generally decreased while biologic therapy use has increased over recent years, there continues to be a significant proportion of PsA and RA patients with moderate/severe disease. Joint burden among PsA patients is slightly lower in comparison to RA, although biologic use was higher in the PsA population. Future research should evaluate the correlation in disease activity and biologic use over time. Acknowledgement: This study is sponsored by Corrona, LLC. The Corrona, LLC. RA registry has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, Astra Zeneca, BMS, Crescendo, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: A. Kavanaugh Grant/research support from: Amgen Abbvie Jannsen Pfizer Novartis, J. Griffith Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., C. Karki Employee of: Corrona, LLC, C. Etzel Consultant for: Merk, Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Consultant for: AbbVie, Amgen, BMS, Genentech, GSK, Lilly, Medimmune, Pfizer, Sanofi, Employee of: Corrona, LLC, Speakers bureau: Genentech (for non-branded talk only), J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis and Pfizer, Employee of: Corrona, LLC, A. Ganguli Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc.